Positive faecal immunochemical test predicts the onset of inflammatory bowel disease: A nationwide, propensity score-matched study - Lee, Eunyoung; Lee, Gil Ho; Park, Bumhee; Ahn, Sung Soo; Noh, Choong-Kyun (Frontiers in Immunology, 2023)
Background & Aims: The faecal immunochemical test (FIT), a non-invasive test for screening colorectal cancer (CRC), is being increasingly understood to reflect heightened inflammation. We aimed to investigate the association between abnormal FIT results and onset of inflammatory bowel disease (IBD), a disease characterized with chronic gut mucosal inflammation. Methods: Participants in the Korean National Cancer Screening Program for CRC between 2009–2013 were analysed and divided into positive and negative FIT result groups. The incidence rates of IBD after screening were calculated after excluding cases of haemorrhoids, CRC, and IBD at baseline. Cox proportional hazard analyses were used to identify independent risk factors for IBD occurrence during follow-up, and 1:2 propensity score matching was performed as a sensitivity analysis. Results: In total, 229,594 and 815,361 participants were assigned to the positive and negative FIT result groups, respectively. The age- and sex-adjusted incidence rates of IBD in participants with positive and negative test results were 1.72 and 0.50 per 10,000 person-years, respectively. Adjusted Cox analysis revealed that FIT positivity was associated with a significantly higher risk of IBD (hazard ratio 2.93, 95% confidence interval: 2.46, 3.47, P < .001), which was consistent for both disease subtypes of ulcerative colitis and Crohn’s disease. The results of Kaplan–Meier analysis in the matched population yielded identical findings. Conclusions: Abnormal FIT results could be a preceding sign of incident IBD in the general population. Those with positive FIT results and suspected IBD symptoms could benefit from regular screening for early disease detection.